PROJETO DO JORNAL-LABORATÓRIO O BARATA: EXPERIÊNCIA E RESPONSABILIDADE DA PRODUÇÃO JORNALÍSTICA - SILVA, MARCIO L. D.; GRANEZ, MÁRCIO D. S.; SILVA, MARCIO L. D.; GRANEZ, MÁRCIO D. S.; SILVA, MARCIO L. D.; GRANEZ, MÁRCIO D. S. (Salão do Conhecimento, 2013)
Resumo